1993
DOI: 10.1046/j.1365-2648.1993.18010114.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of competence in clinical practice: a phenomenological approach*

Abstract: Using a phenomenological approach, this study explores the different dimensions of student nurse assessment in clinical practice from the perspective of 10 experienced practitioners. Phenomenology, one of the various types of qualitative research methods, is used to discover and understand the meaning of human life experiences through an analysis of the subjects' descriptions of situations. It is therefore of particular value when addressing the questions posed in the present study: (a) what attributes charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 0 publications
1
40
0
3
Order By: Relevance
“…Trust was represented as students knowing their own limitations, not being over confident and therefore could be trusted to act in a safe way. In her study, Girot (1993b) also noted that a caring and patient focused attitude combined with good communication skills were cited as important components of competence by the ward sisters. It was also noted in the study that the ward sisters acknowledged the difficulty in measuring attitudes as an example of the challenges staff faced when teaching and assessing clinical performance.…”
Section: Nursing Knowledge : Learning As Experiencementioning
confidence: 91%
See 3 more Smart Citations
“…Trust was represented as students knowing their own limitations, not being over confident and therefore could be trusted to act in a safe way. In her study, Girot (1993b) also noted that a caring and patient focused attitude combined with good communication skills were cited as important components of competence by the ward sisters. It was also noted in the study that the ward sisters acknowledged the difficulty in measuring attitudes as an example of the challenges staff faced when teaching and assessing clinical performance.…”
Section: Nursing Knowledge : Learning As Experiencementioning
confidence: 91%
“…Each of the ward sisters described their own experiences of working with and assessing nursing students. The findings of Girot's (1993b) phenomenological study concluded that the characteristics of competence had 'trust' by the senior nurses in the students as a central component. Trust was represented as students knowing their own limitations, not being over confident and therefore could be trusted to act in a safe way.…”
Section: Nursing Knowledge : Learning As Experiencementioning
confidence: 96%
See 2 more Smart Citations
“…Recognito be supported by various studies. Girot (1993) revealed that sisters commented that newly qualified graduates knew nothing and that they actually expected to be "spoon-fed" all the way. Lathlean & Corner (1991) also indicated staff attitudes as a major reason affecting newly registered nurses' competency.…”
Section: Tencymentioning
confidence: 99%